2019
DOI: 10.1111/jbg.12431
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for reproductive traits in connectedness groups of Duroc, Landrace and Yorkshire pigs in China

Abstract: The objective of this study was to estimate group‐ and breed‐specific genetic parameters for reproductive traits in Chinese Duroc, Landrace, and Yorkshire populations. Records for reproductive traits between April 1998 and December 2017 from 92 nucleus pig breeding farms, which were involved in the China Swine Genetic Improvement Program, were analysed. Due to weak genetic connectedness across all farms, connectedness groups consisting of related farms were used. Three, two and four connectedness groups for Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
(57 reference statements)
4
9
3
Order By: Relevance
“…Among them, the estimates of the additive genetic variances were able to help animal breeders measure the genetic variations and determine the response to selection. The estimate of additive genetic variance for TNB was larger than those reported by Zhang et al [9], who estimated additive genetic variances ranging from 0.534 to 0.770 in the connected groups of Large White pigs, and Ye et al [11], who estimated the value of 0.786 in Large White pigs, while smaller than the results obtained by Thekkoot et al [19] and Zhang et al [2], who reported estimated additive genetic variances of 1.529 and 1.480, respectively. The estimate for NBA was similar to TNB, but the difference was that the additive genetic variance for NBA was smaller than that found by Ye et al [11] with a value of 0.786.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Among them, the estimates of the additive genetic variances were able to help animal breeders measure the genetic variations and determine the response to selection. The estimate of additive genetic variance for TNB was larger than those reported by Zhang et al [9], who estimated additive genetic variances ranging from 0.534 to 0.770 in the connected groups of Large White pigs, and Ye et al [11], who estimated the value of 0.786 in Large White pigs, while smaller than the results obtained by Thekkoot et al [19] and Zhang et al [2], who reported estimated additive genetic variances of 1.529 and 1.480, respectively. The estimate for NBA was similar to TNB, but the difference was that the additive genetic variance for NBA was smaller than that found by Ye et al [11] with a value of 0.786.…”
Section: Discussioncontrasting
confidence: 80%
“…Seven economically important traits related to sow efficiency (i.e., TNB, NBA, LBW, ABW, GL, AFS, and AFF) were considered in this study, and the results, such as the influence of environmental factors, the estimates of heritabilities and genetic correlations between different traits, can be used to provide useful information for the further breeding process of the population. Currently, only TNB trait is considered in the dam-line selection index recommended by the China Swine Genetic Improvement Program, more reproductive traits should also be taken into account [9]. Thus, knowledge of genetic correlations of TNB with other economically important prolificacy traits is required 1) The estimation of genetic correlations are shown in above diagonal, and phenotypic correlations are shown in below diagonal.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated heritabilities for litter size traits at birth were low: 0.10 for TNB, 0.16 for NBA, and 0.08 for NSB (Table 2). The values of Irgang et al, 1994;Lopez et al, 2017;Ohnishi & Satoh, 2014;Zhang et al, 2020). We did not investigate the impact of maternal effects on litter size traits at birth because there was a limited number of farrowing records available in this study; nevertheless, the results of previous studies suggested that such maternal effects had a negligible impact on TNB, NBA, and NSB (Lopez et al, 2017;Ogawa et al, 2019a).…”
Section: Heritabilities Of Litter Size Traits At Birthmentioning
confidence: 94%
“…The models in this study do not include some of the typical fixed effects, as seen for estimates of genetic parameters, due to the nature of the datasets. Studies available in the literature commonly use farm, sex, herd-year-season or slaughter plant (in the case of carcass traits) to define their contemporary groups [13,15,33,34]. However, this study dealt with only female pigs that were raised on the same farms from birth to slaughter and were also slaughtered at the same slaughter plant.…”
Section: Statistical Modelsmentioning
confidence: 99%